Yanshanian Orogeny During North China's Drifting Away From the Trench: Implications of Numerical Models. Issue 12 (30th November 2020) - Yang, Ting; Liu, Shaofeng; Guo, Peng; Leng, Wei; Yang, An
Abstract: Tectonics in North China and adjacent areas were dominated by the Pacific Plate subduction since the Jurassic. Although the extension‐dominated tectonics in North China since the Early Cretaceous can be well explained by the Pacific Plate subduction, it is still not well understood why North China and adjacent areas underwent intense compression (Yanshanian orogeny) during the Late Jurassic and why these regions rapidly switched to extension‐dominated tectonics during the Early Cretaceous. Plate reconstructions suggest that East Asia was moving rapidly in the direction opposite the trench during the Jurassic when North China was undergoing strong compressional deformation. This relationship between back‐arc deformation and overriding plate's motion seems to contradict previous compilations and geodynamic models. We suggest that large‐scale mantle convection and exotic terrane accretions along the East Asian margin have jointly contributed to the Yanshanian orogeny across North China during the Jurassic. We verify this hypothesis with numerical geodynamic models. Our numerical experiments also suggest that large‐scale downwelling mantle flow beneath Asia has promoted continued subduction beneath the Asian margin despite the subduction was often punctuated by collisional and accretionary events. Key Points: North China and adjacent areas suffered strong compressional tectonics when they were drifting in the direction opposite the trench Exotic terrane accretion and large‐scale mantle convection jointly contributed to the strong compression in North China Large‐scale mantle convection promoted long‐term, continued subduction beneath the Asian margin